Lithium-Ion Transport Behavior in Thin-Film Graphite Electrodes with SEI Layers Formed at Different Current Densities - Rangom, Yverick; Duignan, Timothy T; Zhao, X. S (ACS applied materials & interfaces, 2021)
There has been rapidly growing interest in developing fast-charging batteries for electric vehicles. The solid electrolyte interphase (SEI) layer formed at the graphite/electrolyte interface plays an important role in determining the lithiation rate of lithium-ion batteries (LIBs). In this work, we investigated lithium-ion transport behavior in thin-film graphite electrodes with different graphite particle sizes and morphologies for understanding the role of the SEI layer in fast charging LIBs. We varied the properties of the SEI by changing the current rate during the SEI formation. We observed that forming the SEI layer at a much higher current density than is traditionally used leads to a substantial reduction in electrode impedance and a corresponding increase in ion diffusivity. This enables thin-film graphite electrodes to be charged at current rates as high as 12 C (i.e., about 5 min charging time), demonstrating that graphite is not necessarily prevented from fast charging. By comparing the SEI layers formed at different current densities, we observed that lithium-ion diffusivity across the SEI layer formed on a 23 μm commercial graphite at a current density currently used in the industry (e.g., 0.1 C) is approximately 8.9 × 10–10 cm2/s.